Dust off Those Encyclopedias: Using Reference Sources to Teach the ACRL Framework Concepts. Issue 2 (3rd July 2017) - Green, Kristin E. C.
ABSTRACT: What if the ideal tools for teaching undergraduate students the most critical information literacy concepts have been sitting in the stacks all along collecting dust? Reference sources are an optimal medium to introduce all six of the Association of College & Research Libraries' (ACRL) Framework's central concepts for information literacy. Additionally, by understanding a reference source's place in the information search process, students learn to consciously avoid the common pitfall of neglecting exploratory research before specifying research inquiries. Thus, incorporating reference sources thoughtfully into instructional design contributes to the development of both information literacy and metacognition.